Treatments for Iron Deficiency (ID): Prospective Organic Iron Fortification - Wan, Dan; Wu, Qinghua; Ni, Hengjia; Liu, Gang; Ruan, Zheng; Yin, Yulong (Current Pharmaceutical Design, 2019)
Iron deficiency, one of the most common nutritional deficient disorders, frequently affects infants, adolescents and pregnant women and impairs growth, development and immune responses. Iron deficiency may also be secondary to gastrointestinal conditions such as gastrectomy and inflammatory bowel disease, as well as cancer and chronic uremia. Iron supplementation is the most commonly selected treatment option for iron deficiency. This review summarizes the iron compounds currently recommended for the iron fortification of foods and for clinical use. Additionally, this review discusses and compares the important aspects of high-quality iron compounds/products and classes of compounds that enhance iron bioavailability. The development of efficient iron fortification methods remains the most cost-effective and long-term approach to the treatment of iron deficiency or related anemia. To date, no orally administered options for iron fortification can sufficiently replace the parenteral administration of iron supplements, which includes the intramuscular injection of iron-dextran to neonatal piglets and intravenous injection of iron supplements to patients with gastrointestinal disorders. Iron bioavailability may be enhanced by encouraging customers to ingest iron-enriched foods together with dietary sources of vitamin C, folic acid and/or oligosaccharides.
Keywords: anemia